Techniques in contemporary book illustration - Huggins, Linda Wreford (Rhodes University, Faculty of Humanities, Department of Fine Art, 1986)
Introduction: Although the hackneyed adage "one picture is worth a thousand words" defies proof and begs argument, the basic value of illustration in graphic communications is beyond dispute. Without attempting to put a relative value on illustration as compared with words, we can still be aware of the special effectiveness of images, in accomplishing communication goals. The roots of illustration go hack to prehistoric pictorial art of engraved or painted figures done on stone. The hand print can be interpreted as one of the first attempts at drawing. Prehistoric pictorial art depicted visually what could not be expressed by word or gestures some had religious significance, some the presence of myth, others plainly diadactic, showing daily life, social communication, the magic of the hunt, death, birth, group life and sexual symbolism. Little is known of the vast lapse of time between prehistoric art and the imagery that man devised in the service of developing civilisations at the dawn of history. With steadily increasing demands upon his skills, the artisan's mastery of the tools and materials progressed, so that by the beginning of recorded time he was in possession of the potential elements for printmaking. Yet the importance of communication, as we know it today, only developed centuries later with the motivating force of religion. The print could tell its story to those who could not read or write but could quickly grasp the meaning of a picture.
Keywords: Illustration of books -- History -- 20th century